2021
DOI: 10.12688/gatesopenres.13276.1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of violence among female and male grade eight learners: baseline findings from the Girls Achieve Power (GAP Year) trial across three South African townships

Abstract: Background: South African adolescents experience disproportionally high rates of violence, with lifelong health, social and economic impacts. Few papers present risk factors associated with experiences of adolescent violence. Methods: A baseline cross-sectional survey was done (April 2017 – Sept 2018) with 3432 grade 8 learners in the Girls Achieve Power (GAP Year) trial from 26 high schools in three townships (Soweto and Tembisa, Gauteng and Khayelitsha, Western Cape). Collected data on lifetime experiences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…While not statistically significant, our findings on sexual harassment and exposure to illicit drugs are concerning, however they do align with other studies. Our results confirm findings from Kutywayo et al 54 and Ward et al 16 indicating that both female and male learners are vulnerable to sexual harassment and violence. The Optimus Study school survey 16 , and other South African studies 2,55 also found similar results: one in 10 of young people had experienced unwanted sexual touching by a known or unknown adult in their lifetime 21 .…”
Section: Discussionsupporting
confidence: 92%
“…While not statistically significant, our findings on sexual harassment and exposure to illicit drugs are concerning, however they do align with other studies. Our results confirm findings from Kutywayo et al 54 and Ward et al 16 indicating that both female and male learners are vulnerable to sexual harassment and violence. The Optimus Study school survey 16 , and other South African studies 2,55 also found similar results: one in 10 of young people had experienced unwanted sexual touching by a known or unknown adult in their lifetime 21 .…”
Section: Discussionsupporting
confidence: 92%
“…To date, there is one other publication from the GAP Year baseline data, exploring the experiences of violence among grade eight learners 34 .…”
Section: Data Management and Analysismentioning
confidence: 99%
“…As previously reported [24][25][26]28 , overall, 3432 eligible learners across 26 schools participated in the baseline survey: we included 2383 in the analysis who completed both sections of the survey. In some cases, due to lack of time, learners were unable to complete both components and were excluded from this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This research is part of the Girls Achieve Power Trial (GAP Year) cluster randomized controlled trial (cRCT) conducted in 26 non-fee-paying high schools, in three peri-urban townships of South Africa: Khayelitsha (Western Cape Province), and Soweto and Thembisa (Gauteng Province) [24][25][26][27][28] . GAP Year was seeking to test the effectiveness of a CSE asset-building intervention aiming to reduce school dropout among adolescent girls between grades 8-10 while shifting gender attitudes and encouraging positive behaviour change among adolescent boys 27 .…”
Section: Study Design and Settingmentioning
confidence: 99%